THE EFFECT OF APPLYING CLUSTERING TECHNIQUE ON THE STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH - Muhammad Yusuf and Amrin Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study attempts to investigate the effect of applying clustering technique on the students’ achievement in writing descriptive paragraph. The research design of this study was an experimental one. The population of this study was grade VII of MTSs Al Abraar totaling to 60 students of two parallel classes. The data were obtained from random sampling technique through lottery. The class VII-A became the experimental group and was given the treatment by using clustering technique while class VII-B became control group and was given treatment without using clustering technique. The instrument of collecting data was writing test and inter-rater was used to obtain the reliability of the test. The data were analyzed by using t-test formula. It was also obtained that tobserved is higher than ttable (1.760 > 1.673) at the level of significance (α = 0.05) and degree of freedom (df) = 58. It means that null hypothesis was successfully rejected and alternative hypothesis was accepted. As the conclusion, there is a significant effect of applying clustering technique on the students’ achievement in writing descriptive paragraph.